2017
DOI: 10.1097/sla.0000000000001828
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of Postoperative Morbidity After Esophagectomy for Esophageal Cancer

Abstract: These results indicate that postoperative infectious complications may worsen patient prognosis after esophagectomy. Performing esophagectomy without postoperative complications, especially pneumonia, may be beneficial for improving survival outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
140
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 190 publications
(148 citation statements)
references
References 27 publications
5
140
3
Order By: Relevance
“…This finding may highlight the utility of NCCRP1 for stratifying patients at risk of adverse prognosis independent of the TNM staging system. Since findings of the JCOG9907 phase III study comparing the survival benefit of pre-or postoperative cisplatin plus fluorouracil in clinical stage II/III ESCC demonstrated the superiority of neoadjuvant chemotherapy, neoadjuvant cisplatin plus fluorouracil followed by esophagectomy has been the standard treatment for patients with ESCC in Japan (19,20). In this study, we found that the prognostic impact of NCCRP1 expression was similar between patients who received neoadjuvant chemotherapy and those who did not.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…This finding may highlight the utility of NCCRP1 for stratifying patients at risk of adverse prognosis independent of the TNM staging system. Since findings of the JCOG9907 phase III study comparing the survival benefit of pre-or postoperative cisplatin plus fluorouracil in clinical stage II/III ESCC demonstrated the superiority of neoadjuvant chemotherapy, neoadjuvant cisplatin plus fluorouracil followed by esophagectomy has been the standard treatment for patients with ESCC in Japan (19,20). In this study, we found that the prognostic impact of NCCRP1 expression was similar between patients who received neoadjuvant chemotherapy and those who did not.…”
Section: Discussionsupporting
confidence: 55%
“…Patients were questioned to determine their levels of alcohol consumption, and excessive alcohol consumption was defined as >210 g/week for ≥3 years (18). Since 2006, neoadjuvant chemotherapy (fluorouracil combined with platinum-based drugs) was administered to patients with clinical stage II/III ESCC unless contraindicated by the patient's condition or patient refusal (19,20). Postoperative follow-up examinations included physical examination, measurement of serum tumor markers every 3 months, and enhanced computed tomography of the chest and abdominal cavity every 6 months.…”
Section: Methodsmentioning
confidence: 99%
“…Evaluation of variables associated with disease-specific survival using the Kaplan-Meier method with the log-rank test. Postoperative pneumonia after thoraco-abdominal esophagectomy has been reported to be associated with a poor prognosis (15,16). Markar et al reported an association between severe anastomotic leakage and a poor prognosis from 2,944 surgically treated esophageal cancer patients (17).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a totally transmediastinal procedure, if it could be applied safely for esophageal cancer surgery, would be an ideal approach to minimize surgical invasiveness and reduce pneumonia after surgery. Recent studies indicated that pneumonia after esophagectomy may have a negative impact on overall survival, which strongly suggests that the transmediastinal approach might reduce morbidity and prolong survival.…”
Section: Benefits and Limitations Of The Transmediastinal Approachmentioning
confidence: 99%
“…Transthoracic esophagectomy (TTE) has been the standard procedure for ESCC because it allows for extensive mediastinal lymphadenectomy . However, TTE is highly invasive, especially for elderly or comorbid patients, who represent a major population for radical surgery, and it is associated with high morbidity, especially pulmonary complications . Thoracoscopic TTE is widely accepted as a minimally invasive surgery for esophageal cancer, and in a recent randomized control trial, it was reported to have equivalent curability to and less risk for postoperative pneumonia than open surgery …”
Section: Introductionmentioning
confidence: 99%